Lipid Nanoparticles for Organ-Specific mRNA Therapeutic Delivery - Magdalena M. Żak; Lior Zangi (MDPI AG, 2021)
Advances in the using in vitro transcribed (IVT) modRNA in the past two decades, especially the tremendous recent success of mRNA vaccines against SARS-CoV-2, have brought increased attention to IVT mRNA technology. Despite its well-known use in infectious disease vaccines, IVT modRNA technology is being investigated mainly in cancer immunotherapy and protein replacement therapy, with ongoing clinical trials in both areas. One of the main barriers to progressing mRNA therapeutics to the clinic is determining how to deliver mRNA to target cells and protect it from degradation. Over the years, many different vehicles have been developed to tackle this issue. Desirable vehicles must be safe, stable and preferably organ specific for successful mRNA delivery to clinically relevant cells and tissues. In this review we discuss various mRNA delivery platforms, with particular focus on attempts to create organ-specific vehicles for therapeutic mRNA delivery.